Integrasi Edukasi Lingkungan dalam Program Kampus Mengajar : : Studi Kasus Di SMPN 2 Merawang - Fika Dewi Pratiwi; Rani Anggraini; Amanda Puspa Nasir; Ayu Nursyifa (Jurnal Kemitraan Masyarakat, 2024)
The "Kampus Mengajar" program at SMPN 2 Merawang is implemented by students from the University of Bangka Belitung to raise awareness and enhance students' skills in plastic waste management. Through an educational and collaborative approach, this program encourages students to better understand the impact of plastic on the environment. The main activities include socialization on plastic waste management, the creation of eco-bricks, and participation in co-curricular activities such as an exhibition of student works. The results of the program show an increase in environmental awareness among students, as well as the development of proactive attitudes towards maintaining the cleanliness of the school environment.